Cost of intervention delivery in a lifestyle weight loss trial in type 2 diabetes: results from the Look AHEAD clinical trial - Rushing, J. (Obes Sci Pract, 2017)
OBJECTIVE: The Action for Health in Diabetes (Look AHEAD) trial was a randomized controlled clinical trial to compare the effects of 10 years of intensive lifestyle intervention (ILI) with a control condition of diabetes support and education (DSE) on health outcomes in over 5,000 participants with type 2 diabetes. The ILI had significantly greater weight losses than DSE throughout the trial. The goal of this analysis is to describe the cost of delivering the intervention. METHODS: The ILI was designed to promote weight loss and increase physical activity. It involved a combination of group plus individual intervention sessions, with decreasing frequency of contact over the 10 years. The intervention incorporated a variety of strategies, including meal replacement products, to improve weight loss outcomes. The costs of intervention delivery were derived from staff surveys of effort and from records of intervention materials from the 16 US academic clinical trial sites. Costs were calculated from the payer perspective and presented in 2012 dollars. RESULTS: During the first year, when intervention delivery was most intensive, the annual cost of intervention delivery, averaged (standard deviation) across clinical sites, was $2,864.6 ($513.3) per ILI participant compared with $202.4 ($76.6) per DSE participant. As intervention intensity declined, costs decreased, such that from years 5 to 9 of the trial, the annual cost of intervention was $1,119.8 ($227.7) per ILI participant and $102.9 ($33.0) per DSE participant. Staffing accounted for the majority of costs throughout the trial, with meal replacements and materials to promote adherence accounting for smaller shares. CONCLUSIONS: The sustained weight losses produced by the Look AHEAD intervention were supported by intervention costs that were within the range of other weight loss programmes. Future work will include an evaluation of the cost‐effectiveness of the ILI and will contain additional follow‐up data.